Bahasa Indonesia sebagai simbol identitas nasional - Arsya, Fardan Naufal (Maliki Interdisciplinary Journal, 2025)
This study examines the role of Indonesian language as a symbol of national identity through literature review of academic works from UIN Maulana Malik Ibrahim Malang. Indonesian language functions multidimensionally as a national unifying tool since the Youth Pledge of 1928, character education medium, and cultural diplomacy instrument. The BIPA program demonstrates Indonesian language effectiveness in introducing Pancasila values to the international community. Despite facing globalization challenges, Indonesian language continues to show its existence and adaptability. Indonesian language represents the nation’s face reflecting Pancasila values and needs to be maintained as a strong symbol of national identity.